Economic Sociology and Economic Institutions - Freeland, Bob (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This course is intended to serve as an introduction to sociological analyses of the economy, economic processes, and economic institutions. The central focus is to understand how economic activities are shaped, facilitated, altered, and impeded by social relations and social institutions. The course is divided into three parts. The first focuses on the general notion of the "social embeddedness" of economic activity. The concept of embeddedness originated with Polanyi and came to the forefront of modern economic sociology through the work of Granovetter. It implicitly or explicitly permeates much of the work in this area that has been done over the last twenty years. The basic aim of the readings in this section is to begin to get an idea of the different meanings of embeddedness in order to understand how economic processes are shaped and constituted by social relations. The second part of the course deals with firms, networks, and industrial regions. These can be seen both as specific forms of "embedded" economic relationships and as "alternatives" to more atomized (and perhaps fictitious) market relations. The third part of the course focuses more explicitly on the concepts and types of economic institutions. Here, we examine how different types of economic institutions (state, law, labor markets) shape and constitute economic behavior. We also begin to consider variations across societies in the organization of economic institutions and activities, and the ways in which these forms of organization may facilitate distinctive economic capacities and possibilities.